2020
DOI: 10.1101/2020.09.21.307157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Interpreted Atlas of Biosynthetic Gene Clusters from 1000 Fungal Genomes

Abstract: Fungi are prolific producers of natural products, compounds which have had a large societal impact as pharmaceuticals, mycotoxins, and agrochemicals. Despite the availability of over 1000 fungal genomes and several decades of compound discovery efforts from fungi, the biosynthetic gene clusters (BGCs) encoded by these genomes and the associated chemical space have yet to be analyzed systematically. Here we provide detailed annotation and analyses of fungal biosynthetic and chemical space to enable genome minin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In contrast, SMGC abundance in endophyte genomes appears unrelated to PCWDE content. Overall, our results provide evidence that SMGCs may play a key role in facilitating endophyte colonization of diverse hosts (e.g., through suppression or degradation of host immune responses 17,18 ), further highlighting the importance of symbioses to drive not only speciation and ecological diversification 51 , but chemical biodiversity that can be leveraged for novel pharmaceuticals and agrochemicals 52 .…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, SMGC abundance in endophyte genomes appears unrelated to PCWDE content. Overall, our results provide evidence that SMGCs may play a key role in facilitating endophyte colonization of diverse hosts (e.g., through suppression or degradation of host immune responses 17,18 ), further highlighting the importance of symbioses to drive not only speciation and ecological diversification 51 , but chemical biodiversity that can be leveraged for novel pharmaceuticals and agrochemicals 52 .…”
Section: Discussionmentioning
confidence: 66%
“…In a recent large-scale genome mining study, BGCs of around 1 000 fungal genomes were identified by an automated pipeline showing that the classes Eurotiomycetes and Sordariomycetes encode among the largest numbers of BGCs on average per species (approx. 50) ( Robey et al 2021 ). Within the Sordariomycetes dataset (n = 198), only nine members of the Xylariales were included, with four of them belonging to the Hypoxylaceae , all of which were environmental isolates only tentatively identified to the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…A new atlas of fungal BGCs from 1000 fungal genomes, called Prospect, was also released, which includes gene cluster family assignments for these gene clusters. 31 Finally, databases with curated sets of high-quality genomes, such as the ActDES database for actinomycetes 32 released this year, will make it easier to navigate highquality data when navigating biosynthetic potential of various taxa.…”
Section: Biosynthetic Gene Cluster Databasesmentioning
confidence: 99%